Validitas E-Modul Berbasis Discovery Learning Pada Materi Hidrokarbon Untuk Kelas XI SMA/MA Sederajat - Shelby Salsabila; Erviyenni Erviyenni; Sri Wilda Albeta (Chemistry Education Practice, 2025)
The development of science and technology has had a significant impact on the world of education, including the development of teaching materials. One innovation that can be utilized is the electronic module (E-Module) which is more practical and interactive than conventional teaching materials. This study aims to determine the validity of the Discovery Learning-based E-Module on hydrocarbon material for grade XI of senior high school (SMA/MA) and equivalent. The study uses a 4-D development model (Define, Design, Develop, Disseminate) and is limited to the Develop stage. The instruments used include material and media validation sheets, each of which refers to aspects of content feasibility, Discovery Learning characteristics, language, presentation, appearance, and software utilization. The E-Module was developed using the Heyzine Flipbook platform to create an interesting and non-monotonous learning experience. The research sample used in this study was grade XI IPA in two schools, namely SMAN 1 Bangkinang Kota and SMAN 2 Bangkinang Kota. The results showed that the developed E-Module met the validity criteria with an average material validation score of 96.77% and media validation of 98.38%. Thus, the Discovery Learning-based E-Module on hydrocarbon material is declared very valid and suitable for use in the learning process